Por uma Pedagogia da Infância Oprimida: As crianças e a infância na obra de Paulo Freire - Elydio dos Santos Neto; Maria Leila Alves; Marta Regina Paulo da Silva (EccoS – Revista Científica)
The present study, theoretical, is in a stage of a larger research which aims to contribute to building a Pedagogy of the Oppressed Children. Analyzes the work of Paulo Freire when, where and how the author explained his understanding of childhood and child. Performs in this sense a trace in his works published in Portuguese, starting from the period before his exile in October 1964. Defends the work of Freire as an important theoretical framework for analysis of living conditions of children and thus to form a pedagogical committed to the oppressed childhood, this pedagogy that allows open enough to have children with a look of respect to their peculiarities, needs and rights. Approaches, then, the concept of childhood in Giorgio Agamben on the incompleteness of Paulo Freire in the prospect of formation of a pedagogy designed with children. We conclude that already in his first book, "Educação e atualidade brasileira", 1959, Paulo Freire signals to an understanding of children as protagonists of their / our history.